Arsenic Removal and Biotransformation Potential of Exiguobacterium Isolated From an Arsenic‐Rich Soil of Chhattisgarh, India. Issue 2 (10th December 2015) - Pandey, Neha; Bhatt, Renu
Abstract : The presence of arsenic (As) in soil and groundwater has become a serious environmental issue of various regions of India. A haloalkaliphilic Exiguobacterium sp. (As‐9) was isolated via enrichment culture technique from an arsenic‐rich soil of the Rajnandgaon district in the state of Chhattisgarh, India, and characterized as a novel arsenic removing bacteria. The isolate proved to be capable of growing over a broad range of arsenic concentration and was resistant to relatively high levels of arsenate (700 mM) and arsenite (180 mM). It displayed great potential in removing about 99% arsenic under aerobic conditions from the aqueous environment in ten days at 37°C at 100 rpm. Electron microscopy revealed a fourfold increase in the cell size due to intracellular accumulation of arsenic. Selective enzyme assays confirmed that the two intracellular enzymes, namely arsenate reductase and arsenite oxidase played a significant role in arsenate reduction and arsenite oxidation, respectively, thereby contributing to the effective removal of arsenic. These results provide evidence for the occurrence of two distinct mechanisms involved in arsenic resistance; one via arsenate reduction and the other via arsenite oxidation. Moreover, the study reports for the first time the role of arsenic transforming bacteria from this region which could resist and transform exceptionally high concentrations of arsenic oxyanions. Such metabolically active bacterial strain may find application in the treatment of arsenic contaminated soil and aquifers in the near future. Abstract : Arsenic is a toxic element and is widely present in soil and water. Exiguobacterium could play an important role in the removal and enzymatic transformation of this toxic metalloid. The conversion of the more toxic form of arsenic to the less toxic one would provide a clean and cost‐effective technology for the removal of arsenic from contaminated soils and aquifers.